2014
DOI: 10.1093/toxsci/kfu164
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Improves Mitochondrial Function by Promoting MT1/SIRT1/PGC-1 Alpha-Dependent Mitochondrial Biogenesis in Cadmium-Induced Hepatotoxicity In Vitro

Abstract: Melatonin is an indolamine synthesized in the pineal gland that has a wide range of physiological functions, and it has been under clinical investigation for expanded applications. Increasing evidence demonstrates that melatonin can ameliorate cadmium-induced hepatotoxicity. However, the potentially protective effects of melatonin against cadmium-induced hepatotoxicity and the underlying mechanisms of this protection remain unclear. This study investigates the protective effects of melatonin pretreatment on ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 38 publications
8
70
1
Order By: Relevance
“…Moreover, Guo et al . demonstrated that melatonin pretreatment suppressed cadmium-induced hepatotoxicity by enhancing mitochondrial biogenesis34. We also demonstrated that in a non-diabetic MI/R rat model, melatonin treatment significantly reduced cardiac damage by reducing mitochondrial oxidative stress32.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, Guo et al . demonstrated that melatonin pretreatment suppressed cadmium-induced hepatotoxicity by enhancing mitochondrial biogenesis34. We also demonstrated that in a non-diabetic MI/R rat model, melatonin treatment significantly reduced cardiac damage by reducing mitochondrial oxidative stress32.…”
Section: Discussionmentioning
confidence: 61%
“…Secondly, our study is the first to show the arsenite-induced reduction in PGC-1α levels, a transcriptional co-activator which controls mitochondrial biosynthesis [48][49][50]. Previous studies have reported that melatonin improved mitochondrial function by promoting PGC-1α-dependent mitochondrial biogenesis in hepatocytes [51] and skeletal muscle cells [52]. Accordingly, melatonin may maintain mitochondrial mass by increasing PGC-1 levels in arsenite-treated primary cultured cortical neurons.…”
Section: Melatonin Attenuates Arsenite-induced Mitochondrial Lossmentioning
confidence: 54%
“…In addition, in cadmium-induced hepatotoxicity, melatonin exerts positive effects, which are associated with enhanced mitochondrial biogenesis through a SIRT1-dependent PGC-1␣ pathway. This effect appeared to be mediated partially through the binding of melatonin to its MT1 recepor, which activates signaling to mitochondria (Guo et al, 2014).…”
Section: Melatoninmentioning
confidence: 99%